Memorias del curso nacional de producción de trigo. Curso Nacional de Producción de Trigo. Bogotá (Colombia), 22-26 Oct 1990. - Instituto Colombiano Agropecuario, Bogotá (Colombia) (Instituto Colombiano Agropecuario, 1990)
Trigo-Triticum aestivu